PENGEMBANGAN VIDEO PEMBELAJARAN BERBASIS MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) MATERI KEANEKARAGAMAN HAYATI KELAS X SMA - Wahyu Soleha; Arista Ratih; Eko Wulandari (Hira Institute, 2025)
This research is motivated by the lack of development of learning video media for Contextual Teaching and Learning (CTL) models that explain biodiversity material at SMA N 20 Merangin. The learning method is conventional, the media used is Infocus, and the learning resources used are textbooks. The shortcomings of learning methods, media, and learning resources found at SMA N 20 Merangin are still conventional, resulting in students playing a less active role and becoming bored during learning, especially when learning about biodiversity material. These points consider the creation of items within the framework of learning video media for Relevant Contextual Teaching and Learning (CTL) models that are substantial and commonsense for lesson X SMA. This type of inquiry is improvement research using the 4D model. The investigative methods utilized in this investigation are legitimacy surveys and common sense surveys for instructors and students. Five validators approved this investigation to test the legitimacy of learning recordings based on CTL models, specifically four speakers from Merangin College and one science educator from SMA N 20 Merangin. Relevant CTL demonstrate learning video media items, within the perspective of substance possibility, with a 91% (Exceptionally Substantial) rating, introduction midpoints of 91% (Exceptionally Valid), media illustrations midpoints of 95% (Exceptionally Substantial), and an overall number of perspectives of 92% (Very Valid). The learning video item based on the CTL show is additionally complemented by the Learner Worksheet (LKPD). Within the fabric angle, the normal score is 100% (Exceptionally Substantial), the standard dialect score is 87% (Exceptionally Substantial), and the overall number of angles is 93% (Exceptionally Substantial). The common sense test of learning video media based on the Relevant CTL demonstrates an average of 3.91 (Exceptionally Down to Earth) from teachers and an average of 3.31 (Common Sense) from students. Based on the considerations delivered, items are presented in the form of learning video media, based on the Relevant CTL model of biodiversity fabric, which is substantial and down-to-earth for lesson X SMA.